Crystal Growth and Characterization of the Mixed‐Cation Rb+/[XeF5]+ and Cs+/[XeF5]+ Salts. Issue 21 (8th May 2017) - Mazej, Zoran; Goreshnik, Evgeny
Abstract: Invited for the cover of this issue is research led by Zoran Mazej in collaboration with Evgeny Goreshnik, both from the Jožef Stefan Institute, Ljubljana, Slovenia. The cover image shows the formation of a new type of noble gas coordination compounds A[XeF5 ][MF6 ]2 (A = Rb, Cs; M = Sb, Bi) that crystallize in two modifications. Abstract : The reaction between compounds that have been known for a long time can result in new types of coordination compounds that crystallize differently at low and high temperatures… Read more about the story behind the cover in the Cover Profile and about the research itself on page ‐‐ ff (DOI:10.1002/ejic.201700097 ).